2019
DOI: 10.29103/jeru.v2i3.2095
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Pengaruh Pembiayaan Modal Kerja, Pembiayaan Investasi, Dan Pembiayaan Konsumtif Terhadap Total Aset Bank Aceh Periode 2016-2019

Abstract: The study aims to analyze the influence of working capital financing, investment financing, and consumer financing, against the total asset of PT Bank Aceh Syariah. The study uses a quantitative research method, and as a secondary data, utilizes the time-series data. The data collection occurred from September 2016 to March 2019. The hypothesis testing uses multiple linear regression analysis method with the assistance of Statistical Package for The Social Science (SPSS) 22. The partial analysis results (t-tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…This research is supported by a study conducted by Sari (2019), which indicates that NCC financing, represented by ijarah financing, has a positive and significant impact on total assets. Meanwhile, consumptive financing with murabahah contracts in the study by Ahmadsyah et al (2019) has a partially positive and significant impact on the growth of total assets. It can be concluded that the higher the distribution of NCC financing, the better the financial sustainability of a company.…”
Section: The Influence Of Natural Certainty Contracts (Ncc) On Financ...mentioning
confidence: 89%
“…This research is supported by a study conducted by Sari (2019), which indicates that NCC financing, represented by ijarah financing, has a positive and significant impact on total assets. Meanwhile, consumptive financing with murabahah contracts in the study by Ahmadsyah et al (2019) has a partially positive and significant impact on the growth of total assets. It can be concluded that the higher the distribution of NCC financing, the better the financial sustainability of a company.…”
Section: The Influence Of Natural Certainty Contracts (Ncc) On Financ...mentioning
confidence: 89%
“…total aset bank menjadi salah satu parameter yang signi�ikan untuk mengevaluasi kemajuan perbankan syariah dan menentukan sejauh mana kontribusinya terhadap perbankan nasional. Selain berfungsi sebagai indikator kuantitatif yang memberikan gambaran tentang skala suatu bank, total aset juga memberikan pandangan mendalam tentang pengaruh dan kontribusi bank tersebut terhadap keseluruhan sistem perbankan nasional (Ahmadsyah et al, 2019).…”
Section: Indikator Kinerja Bank Total Aset Bankunclassified
“…Islamic Commercial Banks and Islamic Business Units are Islamic banks that are developing in Indonesia. Sharia Banking Statistics data shows that until March 2022 there are 12 Islamic Commercial Banks and 21 Islamic Business Units (Otoritas Jasa Keuangan, 2022). Islamic banking has various types of shari'ah compliant contract and types of usage.…”
Section: Introductionmentioning
confidence: 99%